Pengaruh Metode Role Playing terhadap Hasil Belajar Siswa Kelas V SDN Pandenlamper 03 Semarang - Ernawati, Ernawati; Purnamasari, Veryliana; Estiyani, Estiyani (ISLAMIKA, 2024)
The problem found based on observations of class V students at SDN Pandeanlamper 03 on 17 January 2024 was the lack of students' concentration and students’ involvement in learning process that influenced the students’ learning outcomes. To solve this problem, researchers conducted research in learning process using the role playing method. Therefore, this research aimed to determine the influence of the role playing method on the learning outcomes of class V students at SDN Pandeanlamper 03 Semarang. The focus of this research is Pancasila Education Subject about Diversity as a Gift. The research method used was quantitative using quasy-experiment. The samples of this research were 28 of class V students of SDN Pandeanlamper 03. The collection of data techniques used were test questions which were pretest and posttest and documentation of research activities. The research results gained the average of pretest score was 61.9 before treatment conducted and 83.2 of posttest score after treatment using role playing method conducted. The data analysis results using Normalized Gain showed that the N-Gain is 0.56, this result meant that it was the medium category. T-test showed that t obtained 6.382 > t table 2.056 so that Ha was accepted, meanwhile H0 was rejected and. Therefore, it could be concluded that the role playing method influenced the class V students’ learning outcomes of SDN Pandeanlamper 03 Semarang.